2013
DOI: 10.1056/nejmoa1303729
|View full text |Cite
|
Sign up to set email alerts
|

Family Cluster of Middle East Respiratory Syndrome Coronavirus Infections

Abstract: A human coronavirus, called the Middle East respiratory syndrome coronavirus (MERS-CoV), was first identified in September 2012 in samples obtained from a Saudi Arabian businessman who died from acute respiratory failure. Since then, 49 cases of infections caused by MERS-CoV (previously called a novel coronavirus) with 26 deaths have been reported to date. In this report, we describe a family case cluster of MERS-CoV infection, including the clinical presentation, treatment outcomes, and household relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
445
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(471 citation statements)
references
References 4 publications
12
445
2
12
Order By: Relevance
“…Similarly, the absence of transmission to the community contact may have been due to the case-patient's lack of respiratory symptoms during the 2 meetings. The absence of transmission to household and community contacts in this investigation is similar to that seen in contact investigations of several other patients with MERS (11-13); however, in other settings, transmission to household members who provided care to persons with MERS-CoV infection have been reported, and household clusters have been documented (3)(4)(5)(6)(7)16).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, the absence of transmission to the community contact may have been due to the case-patient's lack of respiratory symptoms during the 2 meetings. The absence of transmission to household and community contacts in this investigation is similar to that seen in contact investigations of several other patients with MERS (11-13); however, in other settings, transmission to household members who provided care to persons with MERS-CoV infection have been reported, and household clusters have been documented (3)(4)(5)(6)(7)16).…”
Section: Discussionsupporting
confidence: 82%
“…While the source or reservoir of MERS-CoV is unknown, the disease is transmitted from person to person, for example by close contacts or in healthcare facilities [17][18][19][20][21][22][23][24]. Based on information related to the first 77 cases, the basic reproduction number of the infection (R0) was estimated to be 0.69 (95% CI 0.50-0.92) at the time [25], indicating a low pandemic potential [26].…”
Section: Human-to-human Transmissionmentioning
confidence: 99%
“…MERS-CoV has a very high mortality rate (2,3). Studies have indicated that this infection can present a wide range of respiratory and non-respiratory symptoms (4)(5)(6)(7)(8)(9). Disease presentations may not start with respiratory symptoms.…”
mentioning
confidence: 99%